Race and Gender in Modern Western Warfare - Ulbrich, David (De Gruyter, 2018)
This book fills a gap in the historiographical and theoretical fields of race, gender, and war. In brief, Race and Gender in Modern Western Warfare (RGMWW) offers an introduction into how cultural constructions of identity are transformed by war and how they in turn influence the nature of military institutions and conflicts. Focusing on the modern West, this project begins by introducing the contours of race and gender theories as they have evolved and how they are employed by historians, anthropologists, sociologists, and other scholars. The project then mixes chronological narrative with analysis and historiography as it takes the reader through a series of case studies, ranging from the early nineteenth century to the Global War of Terror. The purpose throughout is not merely to create a list of so-called "great moments" in race and gender, but to create a meta-landscape in which readers can learn to identify for themselves the disjunctures, flaws, and critical synergies in the traditional memory and history of a largely monochrome and male-exclusive military experience. The final chapter considers the current challenges that Western societies, particularly the United States, face in imposing social diversity and tolerance on statist military structures in a climates of sometimes vitriolic public debate. RGMWW represents our effort to blend race, gender, and military war, to problematize these intersections, and then provide some answers to those problems.